Public & private accounts of help-seeking: The implications of research methods on the presentation of narratives. Issue 4 (4th July 2022) - Dobson, Christina; Russell, Andrew; Brown, Sally; Rubin, Greg
ABSTRACT: For people with symptoms that could indicate cancer, prompt presentation to a health care practitioner facilitates early diagnosis, improves survival, and is encouraged by public health agencies and cancer charities. Nevertheless, time to presentation from symptom onset (the patient interval) is known to vary widely. We report findings from a mixed-methods study examining help-seeking among people with symptoms of lung or colorectal cancer. Patients referred for urgent investigation were invited to complete a questionnaire about their symptoms and help-seeking experiences; 26 of these participants then took part in a semi-structured interview. Discrepant accounts of help-seeking were reported through the different research methods, with longer 'patient intervals' reported in interviews. We use the concept of 'public and private accounts' to reflect upon why socially conforming accounts of early presentation were presented in the questionnaires, whilst accounts of longer 'patient intervals' tended to be presented within an interview encounter.